4×1 Quarter-Circle Notched array antenna with independent feeding for enhanced beam steering mechanism at C-band frequency - Tri Nur Arifin; Ganjar Febriyani Pratiwi; Erfiana Wahyuningsih; Arief Budi Santiko; Suisbiyanto Prasetya; Dian Rusdiyanto; Syah Alam; Yohanes Galih Adhiyoga (SINERGI, 2026)
One of the main challenges in microstrip antenna design is achieving adaptive beam steering. Such mechanism cannot be realized using an antenna array with a corporate feeding technique; instead, each antenna element must be fed independently with specific phase differences to steer the beam as needed. This study aimed to develop a microstrip antenna that can adjust its beam direction by applying an independent feeding technique to a 4×1 microstrip array. The theoretical development focused on calculating the required progressive phase shifts for each antenna element to achieve target steering angles. The proposed beam steering mechanism was implemented using a power splitter and 6-bit digital phase shifters connected to each element of the novel array design. This configuration successfully achieved a beam steering range of approximately ±36°, resulting in a total coverage of about 72°. The simulation results showed that the 4×1 array antenna achieved a gain of 10.11 dBi. Fabrication and measurement of the single element antenna with Quarter-Circle Notched (QCN) elements worked at frequency of 3.47 – 3.57 GHz with a bandwidth of 100 MHz. The measured 4×1 QCN array demonstrated performance within 3.32 – 3.75 GHz, achieving a better bandwidth of 430 MHz. The results also demonstrated that optimal gain could be achieved by adjusting the element spacing. Furthermore, variations in phase shift had been shown to enhance the antenna's beam scanning capability beyond theoretical expectations.